2000
DOI: 10.1159/000025027
|View full text |Cite
|
Sign up to set email alerts
|

Human T Lymphotropic Virus I in Indonesia

Abstract: Human T lymphotropic virus I (HTLV-I) is a retrovirus associated with adult T cell leukemia/lymphoma, tropical spastic paraparesis and possibly with other diseases. The actual incidence of HTLV-I carriers in Asia and Africa is difficult to assess and values of 0–37% have been reported. A study in Papua New Guinea by Yamaguchi et al. [6]found 1.8% positive for antibody to HTLV-I and this area is geographically close to the eastern part of Indonesia. A collaborative study was carried out to establish the seropre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, the situation regarding the HTLV-1 prevalence in the most populated countries has been poorly described. In Indonesia, the few studies revealed no HTLV-1 carrier among the blood donors tested (Tanggo et al, 2000). In Philippines, anecdotal, and ancient study suggested that the infection is present in the general population (Ishida et al, 1988).…”
Section: Htlv-1 Worldwide Distribution and Prevalence Estimates By Gementioning
confidence: 99%
“…However, the situation regarding the HTLV-1 prevalence in the most populated countries has been poorly described. In Indonesia, the few studies revealed no HTLV-1 carrier among the blood donors tested (Tanggo et al, 2000). In Philippines, anecdotal, and ancient study suggested that the infection is present in the general population (Ishida et al, 1988).…”
Section: Htlv-1 Worldwide Distribution and Prevalence Estimates By Gementioning
confidence: 99%